Making Catholic America: Religious Nationalism in the Gilded Age and Progressive Era. By William S. Cossen. Ithaca and London: Cornell University Press, 2023. xi +207 pp. $ 46.95 cloth - Portier, William L. (Church history, 2024)
Making Catholic America: Religious Nationalism in the Gilded Age and Progressive Era. By William S. Cossen. Ithaca and London: Cornell University Press, 2023. xi +207 pp. $ 46.95 cloth. - Volume 93 Issue 3.